Validity of the International Physical Activity Questionnaire (IPAQ) in the elderly: An Integrative Literature Review - Alves Miranda, Kessketlen (2021)
Introduction: The International Physical Activity Questionnaire (IPAQ) has been widely used in research. It is considered a good tool for measuring Physical Activity (PA), however, this questionnaire is not specific for the elderly, it is generally applied to the general population. Objective: To carry out an Integrative Review of Literature presenting the studies that investigated the validity of the IPAQ in the assessment of PA in the elderly in the last six years. Methods: An Integrative Literature Review was carried out in the PUBMED, BVS and SCOPUS databases, for the years 2014 to 2020, using the descriptors: Elderly, Aged, IPAQ questionnaire validity, Physical Activity and Exercise. Results: Eight articles were selected whose methodology presents the validity of the IPAQ, in the evaluation of elderly aged ≥ 65 years, six of the selected articles presented in their methodologies the evaluation performed by the IPAQ-L (long version) and only two articles presented IPAQ- S (short version). Conclusion: The IPAQ-L has been widely used to assess levels of PA and sedentary behavior (SB) in the elderly, evidence shows that the application of the questionnaire combined with accelerometer data has shown satisfactory measurements, however, further versions should be structured to fit this specific audience=population.